Proposal for genetic conservation of Araucaria angustifolia (Parana, Brazil) - Bittencourt, Juliana Vitoria Messias (2010)
The objective of this paper is to summarize genetic concepts developed for plant population restoration and conservation presenting, additionally, a general plan for  Araucaria angustifolia species in the State of Parana (Brazil). Ecological genetics and landscape ecology principles are being used to develop suitable strategies for habitat conservation and restoration. It is not intended that all restoration plans will be established on the base of these principles, but they should be used as guidelines for the formulation of restoration policies focused on key species. Initially this paper gives information about the species and genetic conservation. Then a review of the impact of fragmentation on plant populations is presented, particular by the genetic consequences. The paper describes also the general guidelines for genetic conservation of Araucaria angustifolia in the State of Parana under landscape principles, multi-takeholders and pro-active activities for plant genetic resources conservation.